How to be a very safe maternity unit: An ethnographic study. (February 2019) - Liberati, Elisa G.; Tarrant, Carolyn; Willars, Janet; Draycott, Tim; Winter, Cathy; Chew, Sarah; Dixon-Woods, Mary
Abstract: Maternity care continues to be associated with avoidable harm that can result in serious disability and profound anguish for women, their children, and their families, and in high costs for healthcare systems. As in other areas of healthcare, improvement efforts have typically focused either on implementing and evaluating specific interventions, or on identifying the contextual features that may be generative of safety (e.g. structures, processes, behaviour, practices, and values), but the dialogue between these two approaches has remained limited. In this article, we report a positive deviance case study of a high-performing UK maternity unit to examine how it achieved and sustained excellent safety outcomes. Based on 143 h of ethnographic observations in the maternity unit, 12 semi-structured interviews, and two focus groups with staff, we identified six mechanisms that appeared to be important for safety: collective competence; insistence on technical proficiency; monitoring, coordination, and distributed cognition; clearly articulated and constantly reinforced standards of practice, behaviour, and ethics; monitoring multiple sources of intelligence about the unit's state of safety; and a highly intentional approach to safety and improvement. These mechanisms were nurtured and sustained through both a specific intervention (known as the PROMPT programme) and, importantly, the unit's contextual features: intervention and context shaped each other in both direct and indirect ways. The mechanisms were also influenced by the unit's structural conditions, such as staffing levels and physical environment. This study enhances understanding of what makes a maternity unit safe, paving the way for better design of improvement approaches. It also advances the debate on quality and safety improvement by offering a theoretically and empirically grounded analysis of the interplay between interventions and context of implementation. Highlights: Maternity care continues to be a site of avoidable serious harm. An ethnographic case study identified mechanisms linked to maternity safety. Context and intervention are co-constitutive: neither alone is fully explanatory. Structural influences on safety are of enduring relevance.